Kontribusi Sektor Primer Dan Sektor Sekunder Terhadap Pertumbuhan Ekonomi Kabupaten Madiun - Indartini, Mintarti; Pratiwi, Dian; Rahayu, Endang Edi (Universitas Merdeka Madiun, 2021)
Abstract— The research objective to analyzes the contribution of the primary and secondary sectors to the GRDP of Madiun Regency, analyzes the direction of the relationship between the primary and secondary sectors toward economic growth and analyzes the effect of the contribution of the primary and secondary sectors on the economic growth of Madiun Regency in 2014 - 2018. The data used in this study are (1) Gross Regional Domestic Product (GRDP) aggregate primary and secondary sectors/sub-sectors is the total value added (products) generated by various primary and secondary sectors/sub-sectors which has carried out business or activities in an area without regard to the selection of production factors for the data of 2014 - 2018 (2) GRDP based on the prevailing prices of the primary sector and the secondary sector of Madiun Regency based on the field of business data in 2014 - 2018. Research results that (1) The contribution of the primary sector which contributed the first is the agriculture, forestry and fisheries category, followed by mining and quarrying in Madiun Regency. (2) The contribution of the secondary sector which contributed the first is the construction category, followed by the processing industry, water supply and the lowest is electricity, gas procurement in Madiun Regency. (3) The direction of relations of each sector is positive. (4) Partially, each sector does not significantly influence the rate of economic growth in Madiun Regency. (6) Simultaneously the primary and secondary sectors have a significant effect on economic growth variables in Madiun Regency in 2014-2018. Keywords—: Primary Sector; Secondary Sector; Economic Growth; Madiun Regency.